A peer-led, community-based rapid HIV testing intervention among untested men who have sex with men in China: an operational model for expansion of HIV testing and linkage to care. (12th June 2014) - Yan, Hongjing; Zhang, Renjie; Wei, Chongyi; Li, Jianjun; Xu, Jinshui; Yang, Haitao; McFarland, Willi
Abstract : Objectives: To examine outcomes of a peer-led, community-based intervention providing rapid HIV testing and case management for linkage to care for untested men who have sex with men (MSM) in China. Methods: Rapid HIV testing was performed by trained peer volunteers of a community-based organisation (CBO) in three cities of Jiangsu province at MSM-oriented venues. MSM screened positive were referred and accompanied to local government health agencies (Centres for Disease Control and Prevention (CDC)) for confirmatory HIV testing and provided social support for up to 1 month. Data for the programme were compared with sentinel surveillance surveys of MSM conducted by the national and provincial CDC in the province during the same year to assess differences in the populations reached, in HIV positivity, and linkage to HIV care. Results: A total of 512 previously untested MSM were tested by the CBO programme in 6 months. Compared with those in the surveillance surveys, MSM tested by the CBO were significantly more likely to be younger, single, non-resident of the province, more educated and used condoms less frequently. Higher proportions of HIV-positive MSM screened by the CBO received their confirmatory test results (98.1% vs 72.6%, p<0.001) and linked to care (90.4% vs 42.0%, p<0.001). Conclusions: Trained peers providing rapid HIV testing with social support and case management through the early period following diagnosis can efficiently expand HIV testing and improve linkage to care among MSM in China.